Effect of mass wasting on soil organic carbon storage and coastal erosion in permafrost environments - Obu, Jaroslav (jaroslav.obu@awi.de) (2015)
Accelerated permafrost thaw under the warming Arctic climate can have a significant impact on Arctic landscapes. Areas underlain by permafrost store high amounts of soil organic carbon (SOC). Permafrost disturbances may contribute to increased release of carbon dioxide and methane to the atmosphere. Coastal erosion, amplified through a decrease in Arctic sea-ice extent, may also mobilise SOC from permafrost. Large expanses of permafrost affected land are characterised by intense mass-wasting processes such as solifluction, active-layer detachments and retrogressive thaw slumping. Our aim is to assess the influence of mass wasting on SOC storage and coastal erosion. We studied SOC storage on Herschel Island by analysing active-layer and permafrost samples, and compared non-disturbed sites to those characterised by mass wasting. Mass-wasting sites showed decreased SOC storage and material compaction, whereas sites characterised by material accumulation showed increased storage. The SOC storage on Herschel Island is also significantly correlated to catenary position and other slope characteristics. We estimated SOC storage on Herschel Island to be 34.8 kg C m-2. This is comparable to similar environments in northwest Canada and Alaska. Coastal erosion was analysed using high resolution digital elevation models (DEMs). Two LIDAR scanning of the Yukon Coast were done in 2012 and 2013. Two DEMs with 1 m horizontal resolution were generated and used to analyse elevation changes along the coast. The results indicate considerable spatial variability in short-term coastline erosion and progradation. The high variability was related to the presence of mass-wasting processes. Erosion and deposition extremes were recorded where the retrogressive thaw slump (RTS) activity was most pronounced. Released sediment can be transported by longshore drift and affects not only the coastal processes in situ but also along adjacent coasts. We also calculated volumetric coastal erosion for Herschel Island by comparing a ...